PENGARUH CELAH CAMSHAFT TERHADAP NOISE PADA CYLINDER HEAD HONDA CB 150 R - Indra Hasan; Denur (Jurnal Surya Teknika, 2021)
Noise on a motorcycle is unwanted sound because it does not fit the context of space and time thus affecting ride comfort . Noise caused by the vibrating object or objects collide . Which became the main object causes of noise in the Cylinder Head Honda cb 150 R is due to the large gap camshaft causing collision between the camshaft with holder. This research was conducted entirely in the workshop by examining the influence of several variations of the gap camshaft to noise generated in the cylinder head . Variations slit used was 0,75 mm , 0,85 mm , 0,95 mm , 1,05 mm, and 1,15 mm . The results showed that the variation of the gap camshaft significant effect on the noise generated , namely : a gap of 0,75 mm camshaft generate noise by 78,12 dB , 0,85 mm gap camshaft generate noise with a value of 78,37 dB , 0,95 mm gap camshaft generate noise 78,93 dB , 1,05 mm gap camshaft generate noise levels at 79,95 dB, and 1,15 mm gap camshafts produce 80,23 dB. Based on the results of the research with camshaft gap variation can be concluded that the lowest noise level generated by the camshaft gap of 0,75 mm .